Digital Technologies in Agriculture: Innovations and Prospects - Charshanbiyev Alibek Begxanovich (Scientific Trends, 2025)
This article provides information on the importance of the widespread use of digital technologies in agriculture, not only in improving state and public administration, but also in creating great convenience for people in the social sphere and agriculture, improving the quality of products and services, and reducing unnecessary costs.
Keywords: Agriculture, digital technology, internet of Things, artificial intelligence, drones, cloud technologies.